Cape Verde: democratic planning and practice - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Cape Verde s second National Environment Action Plan (PANA II), a development programme for the period 2004-2014, outlines strategies for the rational use of natural resources and the sustainable management of economic activities, identifying developmen